2021
DOI: 10.7150/jca.51099
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Plays a Carcinogenic Role in EOC via the PI3K/AKT Signaling Pathway in an AR-Dependent Manner

Abstract: Background: Epithelial ovarian cancer (EOC) is one of the most common gynecological cancers with the highest mortality rate. Studies indicate that androgens contribute to initiation or progression of EOC through poorly understood mechanisms, however, in the phase II clinical studies of antiandrogen therapy for EOC, neither flutamide nor bicalutamide showed good antitumor effects. Based on the contradictions, the purpose of this study was to explore the role of androgen receptor (AR) in the androgen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…AR plays an important role in the occurrence and development of sex hormone-dependent tumors. Some studies have indicated that androgen can mediate the overactivation of the phosphatidylinositol-4,5-bisphosphate3-kinase-protein kinase B (PI3K/Akt) signaling pathway and thus promote the proliferation of ovarian cancer cells in an AR-dependent manner ( 44 ). In addition, AR is highly expressed in breast cancer and has carcinogenic potential in ERα-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…AR plays an important role in the occurrence and development of sex hormone-dependent tumors. Some studies have indicated that androgen can mediate the overactivation of the phosphatidylinositol-4,5-bisphosphate3-kinase-protein kinase B (PI3K/Akt) signaling pathway and thus promote the proliferation of ovarian cancer cells in an AR-dependent manner ( 44 ). In addition, AR is highly expressed in breast cancer and has carcinogenic potential in ERα-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that AR could bind directly to the IL12A promoter region to repress transcription, thereby suppressing the cytotoxicity of IL-12-activated NK cells in HCC [ 45 ]. As has been highlighted by scholars, ovarian cancer cell proliferation can also be mediated by the androgen/AR-independent activation of PI3K/AKT [ 46 ].…”
Section: Discussionmentioning
confidence: 99%